2015
DOI: 10.1186/s12943-015-0347-8
|View full text |Cite
|
Sign up to set email alerts
|

Opposing roles for mammary epithelial-specific PPARγ signaling and activation during breast tumour progression

Abstract: BackgroundAmong women worldwide, breast cancer is the most commonly diagnosed cancer, and the second leading cause of cancer-related deaths. Improved understanding of breast tumourigenesis may facilitate the development of more effective therapies. Peroxisome proliferator-activated receptor (PPAR)γ is a transcription factor that regulates genes involved in insulin sensitivity and adipogenesis. Previously, we showed, using 7,12-dimethylbenz [a] anthracene (DMBA)-treated haploinsufficient PPARγ mice, that PPARγ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
0
20
0
1
Order By: Relevance
“…[33][34][35] Some synthetic PPARc ligands, such as rosiglitazone, troglitazone and ciglitazone, inhibit the proliferation of tumour cells and induce tumour cell apoptosis. [36][37][38][39][40] In this study, we found that TNBG-5602 can increase the expression of PPARc at the mRNA and protein levels in vitro and in vivo. Further study found that a PPARc agonist (RSG) can enhance the lipid accumulation of TNBG-5602, while a PPARc inhibitor (T0070907) can reverse the lipid accumulation of TNBG-5602.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…[33][34][35] Some synthetic PPARc ligands, such as rosiglitazone, troglitazone and ciglitazone, inhibit the proliferation of tumour cells and induce tumour cell apoptosis. [36][37][38][39][40] In this study, we found that TNBG-5602 can increase the expression of PPARc at the mRNA and protein levels in vitro and in vivo. Further study found that a PPARc agonist (RSG) can enhance the lipid accumulation of TNBG-5602, while a PPARc inhibitor (T0070907) can reverse the lipid accumulation of TNBG-5602.…”
Section: Discussionmentioning
confidence: 52%
“…It was discovered that overexpression of PPARγ can inhibit cell proliferation and tumour growth, while it is reversed in PPARγ‐silenced cancer cells . Some synthetic PPARγ ligands, such as rosiglitazone, troglitazone and ciglitazone, inhibit the proliferation of tumour cells and induce tumour cell apoptosis …”
Section: Discussionmentioning
confidence: 99%
“…PPAR γ agonists reduce mammary carcinogenesis [17–19], which correlates with induction of PTEN [20, 21] and BRCA1 [22] tumor suppressor activity, as well as reduction of inflammation via the Cox2/Ptgs2 pathway [23]. Conversely, PPAR γ haploinsufficiency [23] or expression of a dominant-negative Pax8-PPAR γ transgene [24] and direct or indirect inhibition of PPAR γ [21, 25] enhance DMBA mammary carcinogenesis. In MMTV-Pax8-PPAR γ mice, the increased rate of carcinogenesis correlates with enhanced Wnt, Ras/Erk, and PDK1/Akt signaling, reduced PTEN expression, and a more stem cell-like phenotype [24].…”
Section: Pparδ and Tumorigenesismentioning
confidence: 99%
“…In this study, some proteins that were found to be related to breast cancer and used in this QSAR are Breast cancer type 1 susceptibility protein, Peroxisome proliferator-activated receptor gamma, STE20-related kinase adapter protein alpha, ATP-binding cassette sub-family G member 2, Human breast cancer cell lines, and Nuclear receptor coactivator 3 (3).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that this gene product initiates cancerous cell migration. Gene expression analyses demonstrate that several of these proteomic hits are differentially expressed between early and advanced stage EOC thus suggesting clinical relevance of these proteins to disease progression (3).…”
Section: Introductionmentioning
confidence: 99%